Digital Inclusion Policies in Higher Education: Perspectives for Ecuador (Docentes 2.0 Journal, 2024)
Digital inclusion in Ecuador is a central axis in the search for an equitable education. The growing integration of Information and Communication Technologies (ICT) in education has posed significant but essential challenges to guarantee digital inclusion in education. The main objective of this essay was to analyze the concept of digital inclusion and its relevance in the Ecuadorian educational field. To do so, primary sources and scientific literature were thoroughly reviewed using a qualitative interpretive approach based on the inductive method and a thematic narrative design. Based on this review, a critical analysis of the technological infrastructure was carried out, considering the Ecuadorian socioeconomic reality. The essay highlights the importance of collaboration between educational institutions, government, and the private sector to promote a more inclusive and digitalized education. This will allow the design of strategies that promote the development of digital skills, essential to face the educational challenges of the 21st century.
Keywords: Digital inclusion policies; education; online learning; digital divide; information technology